A surface-treated perovskite nanocrystal and its preparation method and application
By performing ligand exchange on perovskite nanocrystals and using ligands containing sulfonic acid groups or combinations of acid and amine compound, the problem of poor stability of perovskite nanocrystals is solved, and a high stability and repeatability of perovskite nanocrystal preparation is achieved.
Patent Information
- Application Number
- CN202210977414.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-15
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-08-15
AI Technical Summary
In the prior art, the perovskite nanocrystals have poor stability, especially in high temperature environments, resulting in limited application. At the same time, the binding force of the ligand used in the room temperature preparation method is weak and it is difficult to meet commercial needs.
By ligand exchange reaction of perovskite nanocrystals with ligands containing salts or acids and amino compounds containing sulfonic acid groups, the original ligand is replaced to form a more stable binding of sulfonic acid ligands to perovskite nanocrystals.
The preparation of high-stability perovskite nanocrystals at room temperature is achieved, avoiding the demand for high temperature and inert atmosphere environment, reducing costs, and improving the stability and repeatability of nanocrystals.
Smart Images

Figure CN115197692B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of luminescent materials, and in particular relates to a surface-treated perovskite nanocrystal and a preparation method and application thereof. Background Art
[0002] All-inorganic CsPbX 3 (X=Cl, Br, I) perovskite quantum dots have attracted extensive attention due to their high quantum efficiency, tunable wavelength, simple synthesis method, and high repeatability. However, perovskite halide materials have poor stability and are particularly sensitive to high temperature environments, which severely limits their application.
[0003] Nowadays, the preparation of perovskite nanocrystals mostly adopts the hot injection method. In the hot injection method, the growth of perovskite can be controlled by changing the crystal growth direction and the concentration of the reactants. However, due to the reaction at high temperature, there are very high requirements for the uniformity of temperature control, the uniformity of injection reaction, and energy consumption. In addition, long-chain organic ligands such as oleic acid and oleylamine are required in the process, which are very easy to detach from the surface of perovskite, resulting in reduced quantum efficiency and poor stability. Therefore, for perovskite, it is difficult to scale up the hot injection method to obtain high-quality products exceeding the gram level. In addition, many process strategies for preparing high-stability perovskite nanocrystals at room temperature have been developed. The room temperature method has low cost and high yield, but most of the room temperature preparation methods still use traditional ligands such as oleic acid and oleylamine. Such ligands have weak lattice binding with perovskite and will fall off after being exposed to high temperature for a long time, and the stability does not meet commercial requirements.
[0004] CN110144208A discloses a method for improving APbI 3 The method for improving the efficiency of perovskite quantum dots comprises the following steps: injecting APbI prepared by high temperature hot injection 3 The first purification solvent is added to the quantum dot solution for the first purification, and a first precipitate is obtained after centrifugation; the first precipitate is dispersed in the first organic solvent, a second purification solvent and a ligand are added, and the second precipitate is obtained by centrifugation again; the second precipitate is dispersed in the second organic solvent again to obtain the purified APbI 3 Quantum dots. The ligand is any one of oleic acid, DDAI, NMAI, PMAI and oleylamine iodine. Although this method passivates defects and improves quantum efficiency, the high-temperature hot injection method requires a reaction temperature above 120°C and nitrogen protection. This method is difficult to scale up and has a low yield.
[0005] CN114656961A discloses a method for preparing perovskite quantum dots using ricinoleic acid as a solvent and a ligand, comprising the following steps: dissolving cesium bromide and bismuth bromide in ricinoleic acid, adding octylamine and stirring at room temperature to form a precursor solution, injecting the precursor solution into an anti-solvent ethanol to obtain Cs3 Bi 2 Br 9 Quantum dot solution. This method uses oleic acid ligands and Cs 3 Bi 2 Br 9 The binding force of quantum dots is weak and their stability does not meet commercial requirements.
[0006] Therefore, how to provide a method for preparing room-temperature perovskite nanocrystals to avoid the use of costly hot injection methods while obtaining highly stable perovskite nanocrystals is an urgent problem that needs to be solved. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a surface-treated perovskite nanocrystal and a preparation method and application thereof. The present invention combines the method for preparing perovskite nanocrystals with ligand exchange, and replaces the original ligand on the surface of the nanocrystal with a highly stable sulfonic acid ligand formed by neutralizing an acid containing a sulfonic acid group with an amino compound or directly using a salt containing a sulfonic acid group. The whole process does not require a high temperature, an inert atmosphere environment, or toxic solvents, thus saving costs. The prepared perovskite nanocrystals have high stability, strong repeatability, and are green and environmentally friendly and can be scaled up for production.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing surface-treated perovskite nanocrystals, the preparation method comprising:
[0010] Mixing the perovskite nanocrystals with the ligands at room temperature to perform a ligand exchange reaction to obtain the surface-treated perovskite nanocrystals;
[0011] The ligand includes a salt containing a sulfonic acid group, or a combination of an acid containing a sulfonic acid group and an amine compound.
[0012] The present invention mixes perovskite nanocrystals with specific ligands, and prepares highly stable perovskite nanocrystals through ligand exchange reaction. In the mixing process, the ligands present on the surface of the perovskite nanocrystals will undergo a ligand exchange reaction with a compound containing a sulfonic acid group; compared with the original ligands on the surface of the nanocrystals, such as oleic acid or oleylamine, the sulfonic acid group used in the present invention has a stronger bonding property with the B-site ions (such as Pb ions) on the surface of the perovskite nanocrystals, so a more stable sulfonic acid ligand will be bonded on the surface of the perovskite nanocrystals. Therefore, the perovskite nanocrystals prepared by the present invention have high stability and strong repeatability.
[0013] In the present invention, for the ligand being a salt containing a sulfonic acid group, the neutral property makes the salt containing the sulfonic acid group unnecessary for acid neutralization. After the ligand exchange reaction, the sulfonic acid group with stronger lead binding ability will replace the position of oleic acid and coordinate with lead, and oleate will be generated at the same time. The exchanged sulfonic acid group ligand can improve the stability of perovskite nanocrystals.
[0014] In the present invention, for the ligand comprising a combination of an acid containing a sulfonic acid group and an amine compound, the amine compound will neutralize the acid containing the sulfonic acid group to prevent excessive acidity from causing etching and excessive bonding between the sulfonic acid group and the surface atoms of the perovskite nanocrystal, resulting in the destruction of the structure of the perovskite nanocrystal.
[0015] The method of the present invention can be carried out at room temperature (25±5°C), without the need for high temperature, inert gas environment, or toxic solvents, and can therefore reduce costs and increase efficiency, and is environmentally friendly and can be scaled up for production; at the same time, compared with the use of ligands such as oleylamine or oleic acid alone, the method of the present invention can also make the prepared perovskite nanocrystals have higher stability.
[0016] In the present invention, if the acid containing the sulfonic acid group is not neutralized by the amino compound, the acid will damage the surface of the perovskite nanocrystal, change the surface structure of the perovskite nanocrystal, and cause the perovskite nanocrystal to gradually peel off from the surface and disintegrate.
[0017] Preferably, the salt containing a sulfonic acid group comprises a sodium salt and / or a potassium salt containing a sulfonic acid group, preferably sodium dodecylbenzene sulfonate and / or potassium dodecylbenzene sulfonate.
[0018] Preferably, the acid containing a sulfonic acid group comprises a compound represented by formula (I):
[0019]
[0020] Wherein R is at least one alkyl substituent on the benzene ring, and the alkyl substituent has the general formula C n H 2n+1 , n is not greater than 18, for example, n is 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or 17, etc.
[0021] Preferably, the amine compound includes any one of oleylamine, octylamine, ethylenediamine or didodecylamine, or a combination of at least two thereof.
[0022] Preferably, a combination of an acid containing a sulfonic acid group and an amine compound is used as a ligand, and the mixing is performed in the following manner 1 or 2:
[0023] Method 1 is: adding the acid containing sulfonic acid group and the amine compound to the solution of perovskite nanocrystals respectively, preferably first adding the acid containing sulfonic acid group to the solution of perovskite nanocrystals, stirring at 500-1000 rpm for 3-15 seconds and then adding the amine compound.
[0024] Preferably, the stirring time for adding the acid containing sulfonic acid group is 3-7s.
[0025] Wherein, illustratively, the stirring rate can be 500rpm, 600rpm, 700rpm, 800rpm, 900rpm or 1000rpm, etc.; the stirring time can be 3s, 4s, 5s, 6s, 7s, 8s, 9s, 10s, 11s, 12s, 13s, 14s or 15s, etc., preferably 3-7s.
[0026] In the present invention, the method 1 adds the acid containing sulfonic acid group and the amino compound to the solution of perovskite nanocrystal respectively, wherein the purpose of stirring at 500-1000rpm after adding the acid containing sulfonic acid group is to help the acid containing sulfonic acid group and the oleic acid ligand on the surface of perovskite nanocrystal to replace the reaction more fully through vigorous stirring, and the stirring rate is too large or too small, which will lead to insufficient reaction and affect the degree of conversion of the ligand exchange reaction. Stirring for 3-15s can make the compound containing sulfonic acid group react completely with the oleic acid ligand on the surface of perovskite nanocrystal, and stirring time is too short, which will cause the acid containing sulfonic acid group and the oleic acid ligand on the surface of perovskite nanocrystal to not fully react, and stirring time is too long, which will cause the surface structure of perovskite nanocrystal to be destroyed. Adding the amino compound after stirring can neutralize the acidity in time to prevent the perovskite nanocrystal from being destroyed.
[0027] The second method is to mix an acid containing a sulfonic acid group and an amine compound, and add the obtained mixture to a solution of perovskite nanocrystals.
[0028] In the present invention, in the second method, the acid containing sulfonic acid group and the amino compound are pre-mixed and acid neutralized first, thereby preventing the damage to the perovskite nanocrystalline structure caused by excessive acidity in advance.
[0029] Preferably, a salt containing a sulfonic acid group is used as a ligand, and the mixing is performed in the following manner: the salt containing a sulfonic acid group is directly added to a solution of perovskite nanocrystals.
[0030] In the present invention, a salt containing a sulfonic acid group is used as a ligand. Since the salt solution contains a cation (such as Pb 2+ ) The sulfonic acid ligand has a stronger binding ability, so it can directly coordinate with the B-site cation on the surface of the nanocrystal and replace the original ligand.
[0031] Preferably, the solvent in the solution of the perovskite nanocrystal is an organic solvent, preferably any one of n-hexane, ethanol, acetone or chloroform, or a combination of at least two thereof.
[0032] In the present invention, the type of solvent in the solution of perovskite nanocrystals is not limited, and other organic solvents commonly used in the art for preparing perovskite nanocrystals are also applicable to the present invention.
[0033] Preferably, the ligand exchange reaction is accompanied by stirring, and the stirring time is 0.5-5 h, preferably 1-3 h, for example 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h.
[0034] In the present invention, if the stirring time after all the ligands are added is too short, the ligand exchange reaction will be incomplete, while if the time is too long, the reaction will be completed early, thus wasting time and increasing costs.
[0035] Preferably, the mass ratio of the perovskite nanocrystals to the acid containing sulfonic acid groups is 1:(0.5-20), preferably 1:(3-10), for example 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20, etc.
[0036] In the present invention, if the mass ratio of perovskite nanocrystals to the acid containing sulfonic acid groups is too large, that is, there are too many perovskite nanocrystals, which will cause residual oleic acid or oleylamine ligands on the surface of the perovskite nanocrystals, affecting stability; while if the mass ratio is too small, there are too many acids containing sulfonic acid groups, which will cause the perovskite nanocrystal solution to contain free sulfonic acid ligands, which need to be cleaned and removed later before being used in products, which will increase costs.
[0037] Preferably, the molar ratio of the acid containing a sulfonic acid group to the amine compound is 1:(0.5-3), for example, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5 or 1:3, etc.
[0038] In the present invention, if the molar ratio of the acid containing sulfonic acid group to the amino compound is too small, there will be residual amino compound, and the perovskite nanocrystals will have less binding with the stable sulfonic acid ligand, which is not conducive to the stability of the perovskite nanocrystals; while if the molar ratio is too large, the excess acidity will not be neutralized, which will destroy the crystal structure of the perovskite nanocrystals.
[0039] Preferably, the general formula of the perovskite nanocrystal is ABX 3 .
[0040] Preferably, the ABX 3The A-site cation in the cation includes any one of a cesium ion, a formamidinium ion or a methylamine ion, or a combination of at least two of them.
[0041] Preferably, the ABX 3 The B-site cations include any one of lead ions, tin ions, bismuth ions or germanium ions, or a combination of at least two of them.
[0042] Preferably, the ABX 3 X in the formula (A) is a halogen anion, and the halogen anion includes any one of Cl-, Br- or I-, or a combination of at least two of them.
[0043] In the present invention, ABX 3 Perovskite nanocrystals can be, for example, CsPbBr 3 、CsPbCl 3 、CsSnCl 3 , CsPbI 3 or FAPbBr 3 wait.
[0044] As a preferred technical solution, the preparation method comprises the following steps:
[0045] (I) mixing a salt containing a cation at position A, an acetate, a long-chain organic acid, hexane and propanol to obtain a first precursor solution;
[0046] (II) mixing an alkylamine compound, a hydrohalic acid and propanol, and cooling to room temperature to obtain a second precursor solution;
[0047] (III) Mixing the first precursor solution with the second precursor solution under stirring to obtain ABX 3 Type of perovskite nanocrystals;
[0048] (IV) dispersing the obtained perovskite nanocrystals in a solvent, adding an acid containing a sulfonic acid group, stirring at 500-1000 rpm for 3-7 seconds, adding an amino compound within 3-10 seconds, continuing to stir for 0.5-3 hours, and centrifuging and purifying to obtain surface-treated perovskite nanocrystals, or,
[0049] (IV') dispersing the obtained perovskite nanocrystals in a solvent, adding a pre-mixed mixture of an acid containing a sulfonic acid group and an amine compound thereto, continuing stirring for 0.5-5 hours, and centrifuging and purifying to obtain surface-treated perovskite nanocrystals, or,
[0050] (IV'') Dispersing the obtained perovskite nanocrystals in a solvent, adding a salt containing a sulfonic acid group, continuing to stir for 0.5-5 hours, and centrifuging for purification to obtain surface-treated perovskite nanocrystals.
[0051] In the present invention, the salt of the A-position cation is, for example, cesium acetate, formamidine acetate or methylamine acetate, etc., acetate is, for example, lead acetate, tin acetate, bismuth acetate or germanium acetate, etc., long-chain organic acids are, for example, octanoic acid, heptanoic acid or nonanoic acid, etc., alkylamine compounds are, for example, oleylamine, etc., and hydrohalic acids are, for example, hydrobromic acid, hydrochloric acid or hydroiodic acid, etc.
[0052] In a second aspect, the present invention provides a surface-treated perovskite nanocrystal, wherein the perovskite nanocrystal is prepared by the preparation method of the perovskite nanocrystal according to the first aspect, and the perovskite nanocrystal comprises a perovskite nanocrystal core and a sulfonic acid ligand;
[0053] The sulfonic acid ligand is coordinated with the B-site cation on the surface of the perovskite nanocrystal core, preferably Pb 2+ .
[0054] In a third aspect, the present invention further provides a display device, comprising the perovskite nanocrystal as described in the second aspect.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] (1) In the present invention, surface-treated perovskite nanocrystals are prepared by combining a method for preparing perovskite nanocrystals with specific ligand exchange. On the one hand, the method does not require high temperature or an inert gas environment, can react at room temperature, does not require toxic solvents, saves costs, is green and environmentally friendly, and can be scaled up for production. On the other hand, through the ligand exchange reaction, the original ligand on the surface of the nanocrystal is replaced by a more stable sulfonic acid ligand, which greatly enhances the lattice binding force between the ligand and the perovskite nanocrystal, thereby improving the stability of the perovskite nanocrystal and having strong repeatability.
[0057] (2) After aging at 85° C. for 13 days, the quantum efficiency of the perovskite nanocrystals prepared by the method of the present invention decays from the initial 83% to 61%, and still retains more than 70% of the initial value, that is, the retention value is more than 70%. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 CsPbBr prepared before and after ligand exchange in Example 1 3 Steady-state spectra of perovskite nanocrystals.
[0059] Figure 2 CsPbBr before and after ligand exchange provided in Example 1 and Comparative Example 1 3 Aging diagram of perovskite nanocrystals at 85°C. DETAILED DESCRIPTION
[0060] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0061] Example 1
[0062] This embodiment provides a method for preparing perovskite nanocrystals, the method comprising the following steps:
[0063] (1) Preparation of cesium lead precursor: 40 mL of isopropanol and 25 mL of n-hexane were placed in a conical flask, 0.96 g (5 mmol) of cesium acetate and 1.90 g (5 mmol) of lead acetate trihydrate were added, and then 4.75 mL of octanoic acid (30 mmol) was added, and stirred until the precursor salt was completely dissolved to obtain a cesium lead precursor solution;
[0064] (2) Preparation of bromooleylamine: 9.87 mL (30 mmol) of oleylamine was added to 10 mL of isopropanol, and 3.46 mL of a 48% (30 mmol) hydrobromic acid aqueous solution was slowly added under stirring. After the mixture was cooled to room temperature, a bromooleylamine precursor solution was obtained.
[0065] (3) Pour the bromooleylamine precursor solution into the cesium lead precursor solution under rapid stirring conditions (1000 rpm). The mixed solution immediately turns green under room light, indicating the formation of quantum dots. The reaction is completed after stirring for one minute.
[0066] (4) The solution after the reaction was directly centrifuged (speed 7000 rpm, time 10 min); after the centrifugation, the supernatant was discarded, 50 mL of n-hexane was added to the quantum dot precipitate, and centrifuged again (speed 10000 rpm, time 10 min); after the centrifugation, the precipitate was discarded to obtain 50 mL of CsPbBr 3 Quantum dot ink dispersion (concentration 20 mg / mL);
[0067] (5) Add 50 mL CsPbBr 3 4.89 g (15 mmol) of dodecylbenzenesulfonic acid was added to the quantum dot solution, wherein CsPbBr 3 The mass ratio of quantum dots to dodecylbenzenesulfonic acid was 1:4.89. After stirring at 750 rpm for 5 s, 3.65 mL (15 mmol) of oleylamine was added, wherein the molar ratio of dodecylbenzenesulfonic acid to oleylamine was 1:1, and stirring was continued for 2 h.
[0068] (6) The ligand-exchanged solution is directly centrifuged (rotation speed 10000 rpm, time 10 min) to obtain the ligand-exchanged perovskite nanocrystals.
[0069] Example 2
[0070] This embodiment provides a method for preparing perovskite nanocrystals, the method comprising the following steps:
[0071] (1) Preparation of cesium tin precursor: Place 40 mL of isopropanol and 25 mL of n-hexane in a conical flask, add 0.96 g (5 mmol) of cesium acetate and 1.90 g (5 mmol) of tin acetate trihydrate, then add 4.75 mL of heptanoic acid (30 mmol), and stir until the precursor salt is completely dissolved to obtain a cesium tin precursor solution;
[0072] (2) Preparation of chlorooleylamine: 9.87 mL (30 mmol) of oleylamine was added to 10 mL of isopropanol, and 3.46 mL of a 48% (30 mmol) hydrochloric acid aqueous solution was slowly added under stirring. After the mixture was cooled to room temperature, a chlorooleylamine precursor solution was obtained;
[0073] (3) Pour the chlorooleylamine precursor solution into the cesium tin precursor solution under rapid stirring conditions (800 rpm). The mixed solution immediately turns green under room light, indicating the formation of quantum dots. The reaction is completed after stirring for one minute.
[0074] (4) The solution after the reaction was directly centrifuged (speed 7000 rpm, time 10 min); after the centrifugation, the supernatant was discarded, 50 mL of ethanol was added to the quantum dot precipitate, and centrifuged again (speed 10000 rpm, time 10 min); after the centrifugation, the precipitate was discarded to obtain 50 mL of CsSnCl 3 Quantum dot ink dispersion (concentration 20 mg / mL);
[0075] (5) Add 50 mL CsSnCl 3 1.83 mL (7.5 mmol) of octylamine was added to the quantum dot solution, and after stirring at 500 rpm for 15 s, 6.15 g (15 mmol) of octadecylbenzenesulfonic acid was added, wherein the molar ratio of octadecylbenzenesulfonic acid to octylamine was 1:0.5, and stirring was continued for 5 h;
[0076] (6) The ligand-exchanged solution is directly centrifuged (rotation speed 8000 rpm, time 15 min) to obtain ligand-exchanged perovskite nanocrystals.
[0077] Example 3
[0078] This embodiment provides a method for preparing perovskite nanocrystals, the method comprising the following steps:
[0079] (1) Preparation of cesium lead precursor: 40 mL of isopropanol and 25 mL of n-hexane were placed in a conical flask, 0.96 g (5 mmol) of cesium acetate and 1.90 g (5 mmol) of lead acetate trihydrate were added, and then 4.75 mL of octanoic acid (30 mmol) was added, and stirred until the precursor salt was completely dissolved to obtain a cesium lead precursor solution;
[0080] (2) Preparation of iodoylamine: 9.87 mL (30 mmol) of oleylamine was added to 10 mL of isopropanol, and 3.46 mL of a 48% (30 mmol) hydroiodic acid aqueous solution was slowly added under stirring. After the mixture was cooled to room temperature, an iodoylamine precursor solution was obtained;
[0081] (3) Pour the iodine oil amine precursor solution into the cesium lead precursor solution under rapid stirring conditions (1000 rpm). The mixed solution immediately turns green under room light, indicating the formation of quantum dots. The reaction is completed after stirring for one minute.
[0082] (4) The solution after the reaction was directly centrifuged (speed 7000 rpm, time 10 min); after the centrifugation, the supernatant was discarded, 50 mL of acetone was added to the quantum dot precipitate, and centrifuged again (speed 10000 rpm, time 10 min); after the centrifugation, the precipitate was discarded to obtain 50 mL of CsPbI 3 Quantum dot ink dispersion (concentration 20 mg / mL);
[0083] (5) Add 50 mL CsPbI 3 11.46 g (30 mmol) of dodecylbenzenesulfonic acid was added to the quantum dot solution, wherein CsPbBr 3 The mass ratio of quantum dots to hexadecylbenzenesulfonic acid was 1:11.46. After stirring at 850 rpm for 7 seconds, 10.95 mL (1545 mmol) of didodecylamine was added, wherein the molar ratio of dodecylbenzenesulfonic acid to didodecylamine was 1:1.5, and stirring was continued for 3 hours.
[0084] (6) The ligand-exchanged solution is directly centrifuged (rotation speed 5000 rpm, time 20 min) to obtain the ligand-exchanged perovskite nanocrystals.
[0085] Example 4
[0086] This embodiment provides a method for preparing perovskite nanocrystals, the method comprising the following steps:
[0087] (1) Preparation of lead formamidinium precursor: 40 mL of isopropanol and 25 mL of n-hexane were placed in a conical flask, 0.96 g (5 mmol) of formamidinium acetate and 1.90 g (5 mmol) of lead acetate trihydrate were added, and then 4.75 mL of octanoic acid (30 mmol) was added, and the mixture was stirred until the precursor salt was completely dissolved to obtain a lead formamidinium precursor solution;
[0088] (2) Preparation of bromooleylamine: 9.87 mL (30 mmol) of oleylamine was added to 10 mL of isopropanol, and 3.46 mL of a 48% (30 mmol) hydrobromic acid aqueous solution was slowly added under stirring. After the mixture was cooled to room temperature, a bromooleylamine precursor solution was obtained.
[0089] (3) Pour the bromooleylamine precursor solution into the lead formamidinium precursor solution under rapid stirring conditions (1500 rpm). The mixed solution immediately turns green under room light, indicating the formation of quantum dots. The reaction is completed after stirring for one minute.
[0090] (4) The solution after the reaction was directly centrifuged (speed 7000 rpm, time 10 min). After the centrifugation, the supernatant was discarded, 50 mL of chloroform was added to the quantum dot precipitate, and centrifuged again (speed 10000 rpm, time 10 min). After the centrifugation, the precipitate was discarded to obtain 50 mL of FAPbBr 3 Quantum dot ink dispersion (concentration 20 mg / mL);
[0091] (5) Add 50 mL of FAPbBr 3 2.45 g (7.5 mmol) of dodecylbenzenesulfonic acid was added to the quantum dot solution, wherein CsPbBr 3 The mass ratio of quantum dots to dodecylbenzenesulfonic acid was 1:2.45. After stirring at 1000 rpm for 3 seconds, 3.65 mL (15 mmol) of ethylenediamine was added, wherein the molar ratio of dodecylbenzenesulfonic acid to ethylenediamine was 1:2, and stirring was continued for 1 hour.
[0092] (6) The ligand-exchanged solution is directly centrifuged (rotation speed 3000 rpm, time 30 min) to obtain the ligand-exchanged perovskite nanocrystals.
[0093] Example 5
[0094] The difference between this embodiment and embodiment 1 is that in step (5), 4.89 g (15 mmol) of dodecylbenzenesulfonic acid and 3.65 ml of oleylamine (15 mmol) are pre-mixed and then added to 50 mL of CsPbBr 3 The quantum dot solution was stirred for 2 h.
[0095] The rest of the preparation methods and parameters were the same as those in Example 1.
[0096] Example 6
[0097] The difference between this embodiment and embodiment 1 is that in step (5), only 5.22 g (15 mmol) of sodium dodecylbenzene sulfonate is added to 50 mL of CsPbBr 3 The quantum dot solution was stirred for 2 h and then centrifuged to obtain the supernatant.
[0098] The rest of the preparation methods and parameters were the same as those in Example 1.
[0099] Example 7
[0100] The difference between this embodiment and embodiment 1 is that in step (5), 4.89 g (15 mmol) of dodecylbenzenesulfonic acid is added and the stirring time is 1 s.
[0101] The rest of the preparation methods and parameters were the same as those in Example 1.
[0102] Example 8
[0103] The difference between this embodiment and embodiment 1 is that in step (5), 4.89 g (15 mmol) of dodecylbenzenesulfonic acid is added and the stirring time is 20 s.
[0104] The rest of the preparation methods and parameters were the same as those in Example 1.
[0105] Example 9
[0106] The difference between this embodiment and embodiment 1 is that in step (5), 0.5 g (1.5 mmol) of dodecylbenzenesulfonic acid is added to 50 mL of quantum dot solution, and after stirring at 750 rpm for 5 seconds, 0.37 mL (1.5 mmol) of oleylamine is added, and stirring is continued for 2 hours. The mass ratio of quantum dots to dodecylbenzenesulfonic acid is 1:0.5.
[0107] The rest of the preparation methods and parameters were the same as those in Example 1.
[0108] Example 10
[0109] The difference between this embodiment and embodiment 1 is that in step (5), 20 g (61 mmol) of dodecylbenzenesulfonic acid is added to 50 mL of quantum dot solution, and after stirring at 750 rpm for 5 seconds, 14.84 mL (61 mmol) of oleylamine is added, and stirring is continued for 2 hours. The mass ratio of quantum dots to dodecylbenzenesulfonic acid is 1:20.
[0110] The rest of the preparation methods and parameters were the same as those in Example 1.
[0111] Embodiment 11
[0112] The difference between this embodiment and embodiment 1 is that in step (5), 4.89 g (15 mmol) of dodecylbenzenesulfonic acid is added to 50 mL of the quantum dot solution, and after stirring at 750 rpm for 5 seconds, 0.37 mL (1.5 mmol) of oleylamine is added, and stirring is continued for 2 hours. The molar ratio of dodecylbenzenesulfonic acid to oleylamine is 1:0.1.
[0113] The rest of the preparation methods and parameters were the same as those in Example 1.
[0114] Example 12
[0115] The difference between this embodiment and embodiment 1 is that in step (5), 4.89 g (15 mmol) of dodecylbenzenesulfonic acid is added to 50 mL of the quantum dot solution, and after stirring at 750 rpm for 5 seconds, 18.25 mL (75 mmol) of oleylamine is added, and stirring is continued for 2 hours. The molar ratio of dodecylbenzenesulfonic acid to oleylamine is 1:5.
[0116] The rest of the preparation methods and parameters were the same as those in Example 1.
[0117] Comparative Example 1
[0118] The difference between this comparative example and Example 1 is that in step (5), only 3.75 mL (15 mmol) of oleylamine is added.
[0119] The rest of the preparation methods and parameters were the same as those in Example 1.
[0120] Comparative Example 2
[0121] The difference between this comparative example and Example 1 is that in step (5), only 4.89 g (15 mmol) of dodecylbenzenesulfonic acid is added.
[0122] The rest of the preparation methods and parameters were the same as those in Example 1.
[0123] Comparative Example 3
[0124] The difference between this comparative example and Example 1 is that in step (5), after adding dodecylbenzenesulfonic acid and oleylamine, stirring is continued for 5 minutes.
[0125] The rest of the preparation methods and parameters were the same as those in Example 1.
[0126] Figure 1 The ligand exchanged CsPbBr provided in Example 1 is shown. 3 The steady-state spectrum of perovskite nanocrystals under 420nm excitation light conditions. The quantum efficiency test method of perovskite nanocrystals is as follows. Before the test, the integrating sphere has been calibrated with the standard luminescent sample Rhodamine B. The emission spectra of the blank control and the sample under 420nm excitation light conditions are tested respectively. The quantum efficiency of the sample is measured by calculating the ratio of the number of photons emitted by the sample to the number of photons absorbed.
[0127] from Figure 1It can be seen that the luminescence peak of the perovskite nanocrystals before ligand exchange is 512nm, and the half-peak width is 22nm. The luminescence peak of the perovskite nanocrystals after ligand exchange is 511nm, and the half-peak width is 21nm. There is no obvious change in the luminescence peak position, half-peak width, and luminescence intensity, indicating that the ligand exchange process has no effect on the crystal structure of the nanocrystals. Figure 2 The CsPbBr before and after ligand exchange provided in Example 1 and Comparative Example 1 are shown. 3 The aging data of perovskite nanocrystals at 85℃ shows that the CsPbBr 3 The initial quantum efficiency of perovskite nanocrystals is 83%. After aging for 13 days, the quantum efficiency of Example 1 only drops to about 61%, while the quantum efficiency of Comparative Example 1 drops to about 30% after aging for 2 days. Figure 1 and Figure 2 , it can be seen that the stability of perovskite nanocrystals is significantly improved after ligand exchange.
[0128] Performance Test:
[0129] The perovskite nanocrystals provided by Examples 1-12 and Comparative Examples 1-3 were subjected to an aging test at 85° C. The results are shown in Table 1.
[0130] Table 1
[0131] Retention value of quantum efficiency after aging at 85℃ for 13 days (%) Example 1 73.5 Example 2 72.7% Example 3 71.2% Example 4 73.4% Example 5 73.4% Example 6 73.6% Example 7 71.8% Example 8 41.2% Example 9 43.2% Example 10 71.5% Embodiment 11 39.5% Example 12 35.1% Comparative Example 1 Failure after aging Comparative Example 2 Failure during preparation Comparative Example 3 25.2%
[0132] analyze:
[0133] The data results of Examples 1-12 show that the present invention uses sulfonic acid ligands to perform surface treatment on perovskite nanocrystals, which can improve the stability of perovskite nanocrystals.
[0134] By comparing the data results of Example 1 with those of Examples 5 and 6, it can be seen that premixing can neutralize the acidity of DBSA in advance, protect the perovskite structure from being destroyed, successfully carry out ligand exchange, and improve stability; only adding salts containing sulfonic acid groups can react with perovskite nanocrystals in the solution, thereby improving stability.
[0135] Comparison of the data results of Example 1 with those of Examples 7 and 8 shows that if the stirring time after adding the acid containing the sulfonic acid group is too short, uneven stirring will result in insufficient ligand exchange reaction at the beginning. However, due to the timely addition of oleylamine and long-term stirring to create an exchange environment, the original ligand can eventually be successfully replaced, and the stability is improved. If the stirring time is too long, the acidity of the acid containing the sulfonic acid group will not have time to be neutralized by the amino compound, thereby destroying the surface structure of the nanocrystals, resulting in poor stability of the perovskite nanocrystals.
[0136] By comparing the data results of Example 1 with those of Examples 9 and 10, it can be seen that when too little acid containing sulfonic acid groups is added, an effective concentration difference cannot be formed with the original ligand, so the sulfonic acid groups cannot effectively act on the surface of the nanocrystals to replace the oleic acid or oleylamine ligands, and the stability improvement is not obvious; and when too much acid containing sulfonic acid groups is added, although the stability is improved, the excess free sulfonic acid ligands in the solution of the nanocrystals need to be removed later before they can be used in the product, which will lead to an increase in cost.
[0137] By comparing the data results of Example 1 with those of Examples 11 and 12, it can be seen that if too much amino compound is added, there will be residual amino groups in the solution, which is not conducive to the stability of the perovskite nanocrystals; and if too little amino compound is added, the excess acidity in the acid containing sulfonic acid groups is difficult to neutralize, which will destroy the structure of the perovskite nanocrystals and reduce the stability.
[0138] Comparison of the data results of Example 1 and Comparative Example 1 shows that when only the same amount of oleylamine is added without more stable sulfonic acid ligands for ligand exchange, the weak binding ability of oleylamine ligands leads to poor stability of perovskite nanocrystals and failure of luminescence.
[0139] Comparison of the data results of Example 1 and Comparative Example 2 shows that when only the acid containing the sulfonic acid group is added without adding the amino compound to neutralize its acidity, the strong acidity will destroy the structure of the nanocrystals and cause the perovskite nanocrystals to fail.
[0140] By comparing the data results of Example 1 with those of Comparative Example 3, it can be seen that if the stirring time is too short, the ligand exchange time will be insufficient and the exchange will be incomplete, so the stability of the perovskite nanocrystals will not be improved.
[0141] In summary, the present invention obtains surface-treated perovskite nanocrystals by combining the method for preparing perovskite nanocrystals with specific ligand exchange. On the one hand, the method can react at room temperature, does not require high temperature, inert gas environment, and does not require toxic solvents, thus saving costs, being green and environmentally friendly and capable of scaled-up production; on the other hand, through the ligand exchange reaction, the original ligand on the surface of the nanocrystal is replaced by a more stable sulfonic acid ligand, so that the bond between the sulfonic acid ligand and the B-site cation on the surface of the nanocrystal, such as the Pb ion, is more firmly bonded, thereby improving the stability of the perovskite nanocrystal and having strong repeatability. Compared with the perovskite nanocrystals without ligand exchange, the surface-treated perovskite nanocrystals provided by the present invention have a slight shift in their emission peak position, and there is no significant change in the luminescence peak position, half-peak width, and luminescence intensity, indicating that the ligand exchange process does not affect the crystal structure of the nanocrystals. In addition, when dodecylbenzenesulfonic acid and oleylamine are added in sequence, the surface-treated CsPbBr 3After aging at 85°C for 13 days, the efficiency of the perovskite nanocrystals can still be retained by more than 70%, while the quantum efficiency of the perovskite nanocrystals with only oleamine drops by about 60% after aging for 2 days. Therefore, the stability of the surface-treated perovskite nanocrystals provided by the present invention is significantly improved.
[0142] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing surface-treated perovskite nanocrystals, characterized in that: The preparation method comprises: Mixing the perovskite nanocrystals with the ligands at room temperature to perform a ligand exchange reaction to obtain the surface-treated perovskite nanocrystals; The ligand comprises a combination of an acid containing a sulfonic acid group and an amine compound, wherein the molar ratio of the acid containing a sulfonic acid group to the amine compound is 1:(0.5-3); The preparation method is carried out at room temperature throughout the process; The acid containing a sulfonic acid group includes a compound represented by formula (I): Formula (I) Wherein R is at least one alkyl substituent on the benzene ring, and the alkyl substituent has the general formula C n H 2n+1 , n is not greater than 18; The amino compound is any one of oleylamine, octylamine, didodecylamine or ethylenediamine, or a combination of at least two thereof.
2. The method for preparing surface-treated perovskite nanocrystals according to claim 1, characterized in that: A combination of an acid containing a sulfonic acid group and an amine compound is used as a ligand, and the mixing is performed in the following manner 1 or 2: Method 1 is: adding an acid containing a sulfonic acid group and an amine compound to a solution of perovskite nanocrystals respectively; The second method is to mix an acid containing a sulfonic acid group and an amine compound, and add the obtained mixture to a solution of perovskite nanocrystals.
3. The method for preparing surface-treated perovskite nanocrystals according to claim 2, characterized in that: In the first method, an acid containing a sulfonic acid group is first added to the solution of perovskite nanocrystals, and then the amine compound is added after stirring at a rotation speed of 500-1000 rpm for 3-15 seconds.
4. The method for preparing surface-treated perovskite nanocrystals according to claim 3, characterized in that: The stirring time of adding the acid containing sulfonic acid group is 3-7s.
5. The method for preparing surface-treated perovskite nanocrystals according to claim 2, characterized in that: The solvent in the solution of the perovskite nanocrystal is an organic solvent.
6. The preparation method according to claim 5, characterized in that: The organic solvent is any one of n-hexane, ethanol, acetone or chloroform, or a combination of at least two of them.
7. The method for preparing surface-treated perovskite nanocrystals according to claim 1, characterized in that: The ligand exchange reaction is accompanied by stirring, and the stirring time is 0.5-5h.
8. The method for preparing surface-treated perovskite nanocrystals according to claim 7, characterized in that: The stirring time is 1-3h.
9. The method for preparing surface-treated perovskite nanocrystals according to claim 1, characterized in that: The mass ratio of the perovskite nanocrystal to the acid containing a sulfonic acid group is 1:(0.5-20).
10. The method for preparing surface-treated perovskite nanocrystals according to claim 1, characterized in that: The mass ratio of the perovskite nanocrystal to the acid containing a sulfonic acid group is 1:(3-10).
11. The method for preparing surface-treated perovskite nanocrystals according to claim 1, characterized in that: The preparation method comprises the following steps: (I) mixing a salt containing a cation at position A, an acetate, a long-chain organic acid, hexane and propanol to obtain a first precursor solution; (II) mixing an alkylamine compound, a hydrohalic acid and propanol, and cooling to room temperature to obtain a second precursor solution; (III) mixing the first precursor solution with the second precursor solution under stirring conditions to obtain ABX3-type perovskite nanocrystals; (IV) dispersing the obtained perovskite nanocrystals in a solvent, adding an acid containing a sulfonic acid group, stirring at a speed of 500-1000 rpm for 3-15 seconds, adding an amino compound, continuing to stir for 0.5-5 hours, and centrifuging and purifying to obtain surface-treated perovskite nanocrystals, or, (IV') dispersing the obtained perovskite nanocrystals in a solvent, adding a pre-mixed mixture of an acid containing a sulfonic acid group and an amine compound thereto, continuing to stir for 0.5-5 hours, and centrifugally purifying to obtain surface-treated perovskite nanocrystals; The A-position cation in the ABX3 includes any one of cesium ion, formamidine ion or methylamine ion or a combination of at least two thereof; The B-site cation in the ABX3 includes any one of lead ions, tin ions, bismuth ions or germanium ions, or a combination of at least two thereof; In the ABX3, X is a halogen anion, and the halogen anion includes any one of Cl‾, Br‾ or I‾, or a combination of at least two of them.
12. A surface-treated perovskite nanocrystal prepared by the preparation method according to any one of claims 1 to 11, characterized in that: The general formula of the surface treated perovskite nanocrystal is ABX3; The A-position cation in the ABX3 includes any one of cesium ion, formamidine ion or methylamine ion or a combination of at least two thereof; The B-site cation in the ABX3 includes any one of lead ions, tin ions, bismuth ions or germanium ions, or a combination of at least two thereof; In the ABX3, X is a halogen anion, and the halogen anion includes any one of Cl‾, Br‾ or I‾, or a combination of at least two of them.
13. The surface-treated perovskite nanocrystal according to claim 12, characterized in that: The surface-treated perovskite nanocrystal comprises a perovskite nanocrystal core and a sulfonic acid ligand.
14. The surface-treated perovskite nanocrystal according to claim 13, characterized in that: The sulfonic acid ligand is coordinated with the B-site cation on the surface of the perovskite nanocrystal core.
15. The surface-treated perovskite nanocrystal according to claim 14, characterized in that: The B-site cation is Pb 2+ .
16. A display device, characterized in that: The display device comprises the surface-treated perovskite nanocrystal according to any one of claims 12-15.
Citation Information
Patent Citations
Method for improving efficiency of APbI3 perovskite quantum dots
CN110144208A
Preparation method of passivated inorganic perovskite nanocrystalline
CN114410292A